2014
DOI: 10.3857/roj.2014.32.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive value of liver volume in colorectal cancer patients with unresectable liver metastases

Abstract: PurposeTo determine the prognostic and predictive value of liver volume in colorectal cancer patients with unresectable liver metastases.Materials and MethodsSixteen patients received whole liver radiotherapy (WLRT) between January 1997 and June 2013. A total dose of 21 Gy was delivered in 7 fractions.ResultsThe median survival time after WLRT was 9 weeks. In univariate analysis, performance status, serum albumin and total bilirubin level, liver volume and extrahepatic metastases were associated with survival.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Similar to the results of other prospective and retrospective low-dose WLI studies [ 12 16 20 ], most patients in our trial tolerated combination treatments of low-dose WLI and hyperthermia. Grade III or higher adverse events developed because of either distant or intrahepatic disease progression.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to the results of other prospective and retrospective low-dose WLI studies [ 12 16 20 ], most patients in our trial tolerated combination treatments of low-dose WLI and hyperthermia. Grade III or higher adverse events developed because of either distant or intrahepatic disease progression.…”
Section: Discussionsupporting
confidence: 86%
“…Our group previously reported the results of a retrospective study of WLI as 21 Gy in 7 fractions in 16 patients with hepatic metastasis of colorectal cancer [ 20 ]. Palliation of abdominal pain was acceptable, but median overall survival was only 9 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…32 Jiang et al 33 reported that the increase in ALT was associated with liver metastasis and, thus, a worse prognosis in colorectal cancer cases. In a similar study, Park et al 34 also showed that liver volume and liver function tests were negatively associated with survival in patients with colorectal cancer. Similarly, our study found that serum ALT level at the beginning of follow-up in colon cancer cases was negatively correlated with progressionfree and overall survival time.…”
Section: Discussionmentioning
confidence: 79%